The Beveridge Plan and Local Government Finance - Hicks, J. R.; Hicks, U. K. (Review of Economic Studies, 1943)
Journal Article The Beveridge Plan and Local Government Finance Get access J. R. Hicks, J. R. Hicks Manchester Search for other works by this author on: Oxford Academic Google Scholar U. K. Hicks U. K. Hicks Liverpool Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 11, Issue 1, Winter 1943, Pages 1–19, https://doi.org/10.2307/2967515 Published: 01 December 1943